Increased CEACAM1 expression on peripheral blood neutrophils in patients with rheumatoid arthritis - Matsumoto, Haruki; Fujita, Yuya; Onizawa, Michio; Saito, Kenji; Sumichika, Yuya; Yoshida, Shuhei; Temmoku, Jumpei; Matsuoka, Naoki; Yashiro-Furuya, Makiko; Asano, Tomoyuki; Sato, Shuzo; Suzuki, Eiji; et al. (Frontiers in Immunology, 2022)
Altered expression of adhesion molecules in immune cells has been demonstrated in rheumatoid arthritis (RA). Carcinoembryonic–antigen–related cell–adhesion molecule 1 (CEACAM1) is an adhesion molecule that acts as a coinhibitory receptor in the immune system. We investigated the role of CEACAM1 in immune cell subsets of patients with RA. Peripheral blood was obtained from 37 patients with RA and 20 healthy controls (HC). The expression of CEACAM1 and T–cell immunoglobulin mucin domain molecule (TIM) –3 on peripheral blood mononuclear cells and neutrophils was analyzed by flow cytometry. Intracellular TIM–3 expression was analyzed using cellular lysates by Western blot analysis. Serum levels of soluble CEACAM1 (sCEACAM1) were estimated by an enzyme-linked immunosorbent assay. CEACAM1 expression was not detected in peripheral blood mononuclear cells, including in CD14(+) monocytes and CD3(+) lymphocytes, isolated from patients with RA or HC. However, substantial cell–surface expression of CEACAM1 was detected in peripheral blood neutrophils, and it was significantly elevated in samples from patients with RA without remission compared to those in remission. There was no significant difference in serum levels of sCEACAM1 between patients with RA and HC. Cell-surface expression of TIM-3 was not detected in peripheral blood neutrophils from patients with RA or HC but was seen in CD14(+) monocytes. However, there was no significant difference in TIM–3 expression on monocytes between patients with RA and HC. Our data indicate that cell-surface expression of CEACAM1 on peripheral blood neutrophils are higher in patients with RA and that it is associated with rheumatoid inflammation. Further studies are needed to explore the potential role of CEACAM1 in rheumatoid inflammatory pathways.